2012
DOI: 10.1371/journal.pone.0044771
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Klf5 in Regulating Gene Expression during Post-Eyelid Opening Maturation of Mouse Corneas

Abstract: BackgroundKlf5 plays an important role in maturation and maintenance of the mouse ocular surface. Here, we quantify WT and Klf5-conditional null (Klf5CN) corneal gene expression, identify Klf5-target genes and compare them with the previously identified Klf4-target genes to understand the molecular basis for non-redundant functions of Klf4 and Klf5 in the cornea.Methodology/Principal FindingsPostnatal day-11 (PN11) and PN56 WT and Klf5CN corneal transcriptomes were quantified by microarrays to compare gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 71 publications
(89 reference statements)
2
24
0
1
Order By: Relevance
“…By comparing the WT corneal transcriptomes at PN11 and PN56, we identified 1574 and 1915 genes whose expression decreased and increased, respectively, by more than 2-fold between PN11 and PN56 [32]. Apart from validating the previously identified changes in gene expression during corneal maturation [30, 31], this study identified additional genes whose expression was modulated in the cornea following eyelid opening.…”
Section: Gene Expression During Corneal Developmentmentioning
confidence: 67%
“…By comparing the WT corneal transcriptomes at PN11 and PN56, we identified 1574 and 1915 genes whose expression decreased and increased, respectively, by more than 2-fold between PN11 and PN56 [32]. Apart from validating the previously identified changes in gene expression during corneal maturation [30, 31], this study identified additional genes whose expression was modulated in the cornea following eyelid opening.…”
Section: Gene Expression During Corneal Developmentmentioning
confidence: 67%
“…The inclusion of expression data from separated epithelium, separated stroma, and other epithelial tissues further refined the data. Validating this approach, we observed that known target genes of the transcription factors KLF4 and KLF5 (58,59,72) were located within the same supercluster as Klf4 and Klf5. Our clustering approach allowed us to gain insights into the previously published gene expression data for mice deleted for Klf4 and Klf5 in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…5). For example, cluster A contains the well characterized epithelial differentiation genes Krt12, Aldh3a1, and Upk1b (55-57) and known transcriptional regulators for epithelial differentiation, including Klf4 and Klf5 (58,59). In fact, the KLF5 target genes Dsp and Dsg1b (59) are both found in this cluster.…”
Section: Developmental Co-regulation Of Cornea Genes Suggests New Tramentioning
confidence: 99%
“…Recent years identified a number of transcriptional factors that modulate 4 O. HUBER & I. PETERSEN desmosomal cadherin expression including Stat6, Klf5, Smad4, grainy head-like 1, Foxn1, Cdx1/Cdx2, c-Rel, lymphocyte enhancer factor/transcription factor (LEF/ TCF), and p53/p63 (Ferone et al, 2013;Funakoshi et al, 2008;Johnson et al, 2014;Kenchegowda et al, 2012;Mlacki et al, 2014;Omori-Miyake et al, 2014;Oshiro et al, 2003;Owens et al, 2008;Tokonzaba et al, 2013;Wilanowski et al, 2008). Interestingly, plakoglobin in a complex with LEF-1 is able to bind to the proximal promoter regions of both Dsc2 and Dsc3, however with opposite effects.…”
Section: Transcriptional Regulation Of Desmosomal Cadherinsmentioning
confidence: 99%